2014
DOI: 10.7763/ijesd.2014.v5.511
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Rice Husks and Groundnut Shells for Bioethanol Production

Abstract: Abstract-In the study rice husks and groundnut shells were hydrolysed with 3, 4 and 5% concentrations of dilute hydrochloric acid and the reducing sugar concentration was determined using the dinitrosalicylic acid (DNS) colorimetric method. The concentration of the bioethanol produced was determined using the potassium dichromate method. The results revealed that there is no significance difference (p<0.05) in the yields of the reducing sugar obtained from the substrates at different treatment conditions (0.46… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 4 publications
2
6
0
Order By: Relevance
“…Saccharomyces cerevisiae are seen to be smooth creamish, white spherical shape, Grampositive, non-motile, catalase positive, the organisms was able to ferment glucose, fructose, sucrose, maltose and galactose, producing acid and gas. The result is in agreement with that of Rabah et al [19] who isolated Saccharomyces cerevisiae from palm wine [17] who isolated Saccharomyces cerevisiae from palm wine juice in sake-type fermentation, Moneke et al [30] reported the isolation of Saccharomyces cerevisiae from orchard soil and Tambuwal et al [29] reported the isolation of Saccharomyces cerevisiae from Hibiscus sadriffa (Zobo).…”
Section: Saccharomyces Cerevisiae Isolated From Locally Fermeneted Beverage ("Kunun-zaki") Samplessupporting
confidence: 89%
See 2 more Smart Citations
“…Saccharomyces cerevisiae are seen to be smooth creamish, white spherical shape, Grampositive, non-motile, catalase positive, the organisms was able to ferment glucose, fructose, sucrose, maltose and galactose, producing acid and gas. The result is in agreement with that of Rabah et al [19] who isolated Saccharomyces cerevisiae from palm wine [17] who isolated Saccharomyces cerevisiae from palm wine juice in sake-type fermentation, Moneke et al [30] reported the isolation of Saccharomyces cerevisiae from orchard soil and Tambuwal et al [29] reported the isolation of Saccharomyces cerevisiae from Hibiscus sadriffa (Zobo).…”
Section: Saccharomyces Cerevisiae Isolated From Locally Fermeneted Beverage ("Kunun-zaki") Samplessupporting
confidence: 89%
“…Samples of rotten oranges and locally fermented beverage (kunu-zaki) were collected from minor refuse dumps at the Muda Lawan orange market of Bauchi metropolis for the isolation of Zymomonas mobilis and Saccharomyces cerevisiae. The rotten orange samples were placed in clean sterile polythene bags and locally fermented beverage collected in sterile container and transported immediately to the laboratory for analysis, as described by reference [19].…”
Section: Collection and Processing Of Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Then 1 ml of each biofuel samples were put into test tubes and treated with 2 mL of the chromium reagent. The mixture was allowed to stand for an hour and the absorbance measured at 588 nm using the Ultraviolet-Visible spectrophotometer [14].…”
Section: Determination Of Biofuel Qualitymentioning
confidence: 99%
“…Ethanol is an alternative fuel derived from renewable biological resources. It's a good substitute for gasoline in spark ignition engines [3].…”
Section: Introductionmentioning
confidence: 99%